Bejalai, Strategi Kehidupan dan Pembentukan Komuniti Iban di Tawau, Sabah - Calvin Ligong, Anak Bujang@Endawie (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study is mainly focused on the role of traditional cultural and its traditional economic system of the Iban community which has influenced the Iban community for their migration from their origin to Tawau, Sabah and managed to established their permanent residential area that has been recognized by the Sabah State Government which is known as Kampung Iban Merotai and Kampung Iban Kuala Nansang. The objectives of this study were also comprises of the role of institution of the “Bejalai” culture (Migration Culture) and to access the livelihood strategies of the Iban community in Tawau to sustain their lives as a migrant community. In this study there are 68 of the Iban race respondents whom has involves directly during the fieldwork in Tawau which has been carried out through the research methodology of a set of questionnaire and in-depth interview for the data collection and gathered the first hand of the important information from the respondents for this research and to be analysed. Hence, this study were also shows the interesting factor of the migration trends of the Iban community has go beyond the state boundary and this migration suggestive to the rural to rural migration which the environment were almost similar to their origin residential in Sarawak. The findings of this study shows that the Iban community in Tawau, Sabah are considered as a successful migrant community and able to adapt to the local cultural and able to applied the livelihood strategies through their planning strategies of multi-economic activities and the diversity in their works to enhance the living standards of Iban community. Overall, the establishment of the permanent residential and development of the Iban community in Tawau are mostly influenced by the Traditional Institution of the Iban community which are the “Bejalai” culture itself, the traditional economic system and the traditional agricultural activities which contributes to the Iban community and enable them to established the Successful Migrant Iban community in Tawau, Sabah.